EFFECT OF GREEN INNOVATION ON RENEWABLE ENERGY CONSUMPTION IN NIGERIA - Emmanuel Imuede Oyasor (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2025)
Renewable energy plays a critical role in addressing global energy needs while mitigating climate change. With an emphasis on carbon intensity, domestic credit to the private sector, and electricity accessibility, this study investigates how green innovation affects Nigeria's use of renewable energy. The study uses secondary data from the World Bank Development Indicators (WDI) for the years 1990–2023 and employs an ex post facto design. The statistical link between the dependent variable, renewable energy consumption, and the independent variables, such as carbon intensity (CI), domestic credit to the private sector (DCPS), and access to electricity (AE), is evaluated using a multiple regression analysis. The results show that carbon intensity has no discernible effect on the use of renewable energy, indicating that the adoption of renewable energy is not solely influenced by emissions reduction. Investment in sustainable energy is increased with support. Conversely, access to electricity negatively affects renewable energy consumption, implying that grid expansion may reduce reliance on renewable sources. These results highlight the critical role of financial incentives in promoting renewable energy while underscoring the need for strategic electrification policies. The study recommends that policymakers introduce low-carbon technology incentives, enhance green financing through low-interest loans, and prioritize decentralized renewable energy solutions, such as off-grid solar systems, to ensure sustainable electrification. This information contributes to the broader discourse on green innovation and energy sustainability in Nigeria, offering empirical guidance for policymakers and investors.